Pengorganisasian Media Dakwah - Efendi, Erwan; Azizah, Siti; Ramadhan Sirait, Syahrial; Mulia, Rojas (VISA: Journal of Vision and Ideas, 2023)
Da'wah media management is very important so that da'wah implementers have high media capabilities. It is necessary to organize da'wah media so that the implementation of da'wah can be carried out professionally. The purpose of this study is to determine the form of organizing da'wah media. Researchers use literature research methods by utilizing literature literature, which consists of books, notes, and previous research reports. The results and discussion show that organizing in da'wah media is to gather group members who are willing to work together in a solid group in regulating the tools or da'wah media used to achieve the desired da'wah goals.